If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -14 + -4x = 6x + -9 Reorder the terms: -14 + 6x + -4x = 6x + -9 Combine like terms: 6x + -4x = 2x -14 + 2x = 6x + -9 Reorder the terms: -14 + 2x = -9 + 6x Solving -14 + 2x = -9 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -14 + 2x + -6x = -9 + 6x + -6x Combine like terms: 2x + -6x = -4x -14 + -4x = -9 + 6x + -6x Combine like terms: 6x + -6x = 0 -14 + -4x = -9 + 0 -14 + -4x = -9 Add '14' to each side of the equation. -14 + 14 + -4x = -9 + 14 Combine like terms: -14 + 14 = 0 0 + -4x = -9 + 14 -4x = -9 + 14 Combine like terms: -9 + 14 = 5 -4x = 5 Divide each side by '-4'. x = -1.25 Simplifying x = -1.25
| (4X+7)+(2X-16)= | | 7(4y-9)-(2y+6)= | | 3y-10=x | | u=5(8n+35)+6(n+1) | | 5n+9=3n-1 | | (4c^8d^-6)/8d^3)^-1 | | (4X+7)+(2-16)= | | 5m=18+2m | | log(9x)=1 | | (2+y)(2y+3)=0 | | x=-14+3(4) | | (-4.5)+4.9+3.4= | | 18+10=m | | 2.5x-3(x+1)=12 | | 4x^9n+4=256 | | -70+15y+2y=-2 | | 3/9y-5=-2 | | h=15-8 | | (-5)+(-7.1)= | | 8=-9x+3 | | 4x(5x+3)=2x(7x+6) | | ((60-61)/n)x100=60 | | [-14]= | | a+3b=30 | | 6x+2=8x-12 | | (4n-3)(2n+1)=7 | | 2a+7=23 | | -1/2=2/3v-2/7 | | 2a+12=48 | | 0.25x+24=9 | | 4w+z=5 | | 114.88+-29.36= |